HUBUNGAN PENGETAHUAN DAN SIKAP MASYARAKAT TERHADAP KEPATUHAN PENERAPAN PROTOKOL KESEHATAN PADA MASA PANDEMI COVID-19 DI KABUPATEN JEMBRANA - Cihnawati, Ni Kade Sari; Subrata, I Made (ARCHIVE OF COMMUNITY HEALTH; Vol 10 No 1 (2023): April 2023, 2023)
Coronavirus Disease 2019 (COVID-19) is an infectious disease caused by the Acute Respiratory Syndrome Coronavirus 2 (SARS Cov-2). The community has a role in breaking the chain of transmission of COVID-19 and does not create a source of transmission as a result of interactions between individuals and groups at a point in the location. The purpose of the study was to determine the relationship between individual characteristics knowledge and attitudes towards compliance with the application of health protocols during the COVID-19 pandemic in Jembrana Regency. The design of this study was observational, with adesign cross sectional. The number of samples is 117 people. The sampling technique in this study used non probability sampling, which is a combination of  snowballing and voluntary sampling which was conducted in Jembrana Regency in April-June 2021. The results showed that 77.78% complied with the application of health protocols and 22.22% did not comply. Variables of age, gender, income, last education and attitude have no relationship, age group 18-25 (p = 0.8941; OR = 1.14; 95%CI = 0.42-3.11), age group 26-45 (p= 0.8941;OR= 0.90; 95%CI=0.42-3.11), gender (p=0.2496,OR=1.68;95%CI:0.69-4.03 ), income (p=0.1574;OR=2.2;95%CI :0.69-4.03), last education (p= 0.6508; OR=1.26; 95%CI: 0.45- 3.50). The related variables were knowledge and public attitudes, knowledge (p=0.0032; OR=4.4;95% CI: 1.66-11.66), attitudes (p=<0.001; OR=7, 27; 95%CI: 2.69-19.65). It can be concluded that there is a relationship between knowledge and attitudes towards compliance with the implementation of COVID-19 health protocols. It is recommended to mobilize cadres in each of the Neighborhood Associations to maximize IEC, information communication and education to the public regarding COVID-19 and the implementation of the COVID-19 health protocol which is carried out online. Keywords: Knowledge, Attitude, COVID-19, Health Protocol